TINJAUAN ASPEK KEAMANAN REKAM MEDIS DI RUANGAN FILLING GUNA MENUNJANG EFEKTIVITAS KERAHASIAAN REKAM MEDIS DI RUMAH SAKIT XYZ - Irda Sari; Eneng Pitriyani (Jurnal Infokes, 2023)
Medical record security based on research from the physical, chemical, and biological aspects. The purpose of this study is to determine the safety of medical records in maintaining the confidentiality of room filling. The research method used is qualitative. The research was conducted at XYZ. The tools used in research are interviews and observasion. Data processing techniques used are non-statistical. The researcher concluded that the security of medical records based opn physical, biological, and chemical aspects can be said to be not optimal, because active medical records are still available on the floor in cardboard box. Confidentiality of medical records is contained in the medical records room which has 2 places. Room 1 already uses a fingerprint door to maintain security and confidentiality, room 2 hasn’t used it so you have to pay more attention because in that room the files are confidential. Confidentiality is also not maximized because the filling room has not used a fingerprint door so there are still other officers who can enter the filling room. Special human resources for strorage are still lacking. To improve service quality, there must be additional human resources specifically for storage and optimization of facilities and infrastructure. Keywords: Security, Confidentiality, Medical Records